Prodromal Parkinson’s disease and subsequent risk of Parkinson’s disease and mortality - Xiao Chen; Yaqi Li; Yun Shen; Michael A. Schwarzschild; Xiang Gao (npj Parkinson's Disease)
Abstract Association of prodromal Parkinson’s disease (PD) with risk of PD and risk of mortality in individuals with PD warrant investigation through large-scale prospective study. We included 501,475 participants without PD at baseline. Eight prodromal features were measured. Incident PD cases were identified via hospital admission, death register, and self-report. Cox regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs). Multivariable-adjusted HRs3+vs.0 prodromal PD features and 95%CIs were 3.12 (2.58–3.78) for men and 2.71 (2.11–3.47) for women. Prodromal PD predicted only PD onset occurred during the first 6 years of follow-up (HR3+vs.0 prodromal features = 10.5; 95% CI: 8.60–12.9), but not after 6 years (HR = 1.00; 95%CI: 0.76-1.32). The presence of prodromal PD conferred a higher risk of mortality among participants with PD. Having prodromal PD were associated with higher probability of developing PD in short-term and higher risk of mortality among individuals with PD.